Metagenomics-based analysis of microbial community structure and functional differences in fermented grains of Jiang-flavored baijiu from different production regions and policy recommendations for industrial development - Shen, Jiaqi; Hu, Yuanyan; Zhang, Yunjin; Li, Lixia; Deng, Xiaofeng; Chen, Manjing; Li, Laoda; Xie, Peiyun; Shao, Mingbo (Frontiers in Microbiology, 2025)
IntroductionRecently, some regions that originally focused on strong-flavor baijiu production started producing Jiang-flavored baijiu, providing a new perspective for studying the dynamic changes in the microbial community during brewing.MethodsThis study used second-round fermented grains of Jiang-flavored baijiu from three Guizhou production regions (Renhuai, Duyun, and Bijie). By applying metagenomics technology and various analytical and statistical methods, we analyzed the community structures of bacteria and fungi in fermented grains, their functional genes, and their correlations with environmental factors.ResultsWe identified 1063 bacterial genera and 411 fungal genera. Although the dominant microbial species were similar across regions, their relative abundances differed significantly. α-diversity analysis showed that grains from the Bijie region had higher species richness and evenness indices, indicating the significant impact of geographical location and the strong-flavor baijiu-brewing background on microbial structure and composition. Analysis of similarity and the Wilcoxon rank-sum test revealed significant differences in the microbial communities of different regions, and we identified genera with large differences in abundance, such as Desmospora and Kroppenstedtia among bacteria, and Pyrenophora and Blyttiomyces among fungi. Based on our Kyoto Encyclopedia of Genes and Genomes (KEGG) database analysis, the Duyun region had a significantly higher abundance of metabolism-related genes at the tertiary KEGG level. Redundancy analysis showed that six environmental factors (relative humidity, daily temperature difference, elevation, annual mean temperature, extreme cold temperature, and annual precipitation) exerted complex effects on microbial functional genes in fermented grains. Carbon metabolism, antibiotic biosynthesis, and elevation were positively correlated with microbial functional genes. Actinobacteria are crucial for carbon metabolism, followed by Proteobacteria and Chloroflexi.DiscussionThis study elucidated the structural and functional characteristics of microbial communities in second-round fermented grains of Jiang-flavored baijiu under production area transitions and proposed policy recommendations to promote the differentiated development of the baijiu industry.